Cohesion and Coherence in Students' Thesis Abstract Writing - Beatriz Magdalein Indira Otta; Indah Arvianti; Eko Heriyanto (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2022)
Final-year students should have the ability and competence to write, including in writing their thesis abstracts. Although short, abstract writing must pay attention to several things. One indicator of good writing is marked by using logical, consistent words that are easy to understand. This study aims to identify the types of cohesion (grammatical and lexical) and coherence in writing abstracts for final students of AKI University and whether they have fulfilled cohesive and coherent writing. This study analyzes 16 undergraduate thesis abstracts for the English Literature study program for the 2019-2022 and 2020-2021 academic years. This study uses qualitative and quantitative research methods to achieve this goal. The result shows that the students use lexical cohesion devices much more than grammatical ones. Unfortunately, neither substitution nor ellipsis devices were found. Even so, the students have pretty good competence in making cohesive abstracts. On the other hand, the results of the coherence analysis show that all students have a good understanding of using all aspects of coherence. But even though they use all aspects, not all students succeed in creating coherent writing wholly.